2011
DOI: 10.1002/jssc.201000858
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic nebulization extraction coupled with headspace hollow fiber microextraction of pesticides from root of Panax ginseng C.A. Mey.

Abstract: The ultrasonic nebulization extraction coupled with headspace hollow fiber microextraction (UNE-HS-HFME) was applied for the extraction of pesticides from root of Panax ginseng C.A. Mey. Experimental parameters, which affect the performances of ultrasonic nebulization extraction coupled with headspace hollow fiber microextraction, such as the kind of acceptor solvent in the pore of the fiber wall, the sample amount, extraction time, salt concentration in extraction solvent, pH of the acceptor solution, the elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Proper salt concentration can improve the viscosities of sample solutions and accelerate the mass transfer rate. ,,, In this study, the effect of NaCl concentration in the range of 0–20% on the response signals of analytes was investigated. It can be seen from Figure S4 that the peak areas of all analytes increased with the increase of NaCl concentration until the concentration reached 15%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Proper salt concentration can improve the viscosities of sample solutions and accelerate the mass transfer rate. ,,, In this study, the effect of NaCl concentration in the range of 0–20% on the response signals of analytes was investigated. It can be seen from Figure S4 that the peak areas of all analytes increased with the increase of NaCl concentration until the concentration reached 15%.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Figure S4 that the peak areas of all analytes increased with the increase of NaCl concentration until the concentration reached 15%. However, our previous study indicated that more salt in aerosol particles could cause a change of the physical properties of the fiber wall, which might result in a decrease of the diffusion rates of the analytes . Finally, a 15% NaCl aqueous solution was chosen in the following experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After extraction, the fiber was desorbed in a polar solvent. Li et al [49] described an ultrasonic nebulization extraction coupled to headspace HFME for extraction of pesticides from a plant root sample. A suspension of powdered sample in NaCl solution was nebulized by ultrasound.…”
Section: Applications Of Hfme For Extraction Of Pesticidesmentioning
confidence: 99%